Impingement dynamics of jets in a confined impinging jet reactor - Pal, Sayan; Madane, Ketan; Mane, Mayur; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2021)
The interaction of two impinging liquid jets in a confined impinging jet reactor (CUR) is explored. Multiphase flow simulations were performed using the volume of fluids (VOF) approach to investigate the impingement dynamics of liquid impinging jets, and single-phase CFD simulations have been performed to understand the turbulence and the mixing performance in the system. At identical inlet velocities, the liquid sheet formed on the impingement axis was found to move toward the liquid jet inlet of the lesser density fluid until reaching equilibrium. The formation and transient movement of liquid sheets are characterized for different jet velocities. An improved reactor geometry is proposed that reduces the wall effect on sheet formation and wall deposition on discharge points of jets. Upon breaking away from the impinging film, the two liquid phases are found to be intertwined in the form of ligaments and droplets after fragmentation of the sheet, providing a higher interfacial confirmed by performing high-throughput continuous antisolvent precipitation.

Evaluating suitability of confined impinging jet reactor for exothermic reactions: hydrodynamics, residence time distribution, and heat transfer - Khan, Muzammilanwar S.; Mane, Mayur; Kulkarni, Amol A. (AICHE Journal, 2022)
Effect of confinement (wall proximity) of a confined impinging jet reactor (CIJR) on the flow field, residence time distribution and heat transfer are explored, through experiments and CFD simulations. Hydrodynamic characteristics are evaluated for different parameters namely confinement, impinging jet velocity, temperature gradient, and so on. For 2 mm confinement, highest values of dispersion number and overall heat transfer coefficient are observed due to interaction of turbulent eddies followed by the effect of reactor wall proximity. For the CIJR having confinements above 10 mm, jet velocity need to be greater than 3 m/s to achieve both, excellent mixing efficiency and high heat removal rate. Empirical correlations for Dispersion and Nusselt numbers as a function of Re-j and L/D are obtained, over a range of 500 <= Rej <= 3000\$\$ 500\textbackslashle {\textbackslashmathit{\textbackslashoperatornameRe}}_j\text backslashle 3000 \$\$ and 5 <= L/D <= 35\$\$ 5\textbackslashle L/D\textbackslashle 35 \$\$, which correspond to jet velocity of 0.5-3 m/s. The present study gives a basis for designing CIJR suitable for rapid, homogeneous, exothermic reactions.
Keywords: confinement; exothermic reactions; heat transfer; impinging jets; residence time distribution